FgSsn3 kinase, a component of the mediator complex, is important for sexual reproduction and pathogenesis in Fusarium graminearum - Cao, Shulin (Sci Rep, 2016)
Fusarium graminearum is an important pathogen of wheat and barley. In addition to severe yield losses, infested grains are often contaminated with harmful mycotoxins. In this study, we characterized the functions of FgSSN3 kinase gene in different developmental and infection processes and gene regulation in F. graminearum. The FgSSN3 deletion mutant had a nutrient-dependent growth defects and abnormal conidium morphology. It was significantly reduced in DON production, TRI gene expression, and virulence. Deletion of FgSSN3 also resulted in up-regulation of HTF1 and PCS1 expression in juvenile cultures, and repression of TRI genes in DON-producing cultures. In addition, Fgssn3 was female sterile and defective in hypopodium formation and infectious growth. RNA-seq analysis showed that FgSsn3 is involved in the transcriptional regulation of a wide variety genes acting as either a repressor or activator. FgSsn3 physically interacted with C-type cyclin Cid1 and the cid1 mutant had similar phenotypes with Fgssn3, indicating that FgSsn3 and Cid1 form the CDK-cyclin pair as a component of the mediator complex in F. graminearum. Taken together, our results indicate that FgSSN3 is important for secondary metabolism, sexual reproduction, and plant infection, as a subunit of mediator complex contributing to transcriptional regulation of diverse genes.